2017
DOI: 10.1139/cjm-2016-0733
|View full text |Cite
|
Sign up to set email alerts
|

The development of probiotics for women’s health

Abstract: Abstract:The idea you could use lactic acid bacteria to treat and prevent recurrence of vaginal infections was ridiculed in the early 1980s. Bacteria were the bad guys to be eradicated by current and emerging antibiotic classes. Thirty years later, probiotic administration of microbes is widespread worldwide, including for vaginal and bladder health in women, and the scientific basis and clinical efficacy data for this and multiple other applications prove the viability of this concept. The development of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 92 publications
0
50
0
Order By: Relevance
“…Therefore, the application of beneficial microbes such as Lactobacillus spp. could overcome the presence of pathogens and promote a healthy state to the vaginal microbiome [128]. Over the past years, different evidence has been published acknowledging the clinical relevance of probiotics as an adjuvant component together with antibiotic therapy (Table 1).…”
Section: Probiotics and Microbiota Manipulationmentioning
confidence: 99%
“…Therefore, the application of beneficial microbes such as Lactobacillus spp. could overcome the presence of pathogens and promote a healthy state to the vaginal microbiome [128]. Over the past years, different evidence has been published acknowledging the clinical relevance of probiotics as an adjuvant component together with antibiotic therapy (Table 1).…”
Section: Probiotics and Microbiota Manipulationmentioning
confidence: 99%
“…The common characteristics of BV patients are the decrease of Lactobacillus and the increase of G. vaginalis in the vagina. L. rhamnosus GR-1 was the first probiotic used as a vaginal microbiota regulating Lactobacillus in 1988 [7]. It was demonstrated that L. crispatus could repress the expression of vly and sld genes in G. vaginalis [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The probiotic Lactobacillus rhamnosus GR-1 is bile and acid resistant and can survive passage through the gastrointestinal tract. It has been shown to have a protective effect against urinary tract infections by interfering with the adhesion of urogenital pathogens [5]. This strain is used to produce probiotic yogurt as part of the Western Heads East Initiative (WHE) in Eastern Africa.…”
Section: Introductionmentioning
confidence: 99%